Perubahan Bunyi Bahasa Proto Austronesia ke dalam Bahasa Melayu Riau Dialek Pasir Pengaraian - Sukma, Sukma; Widayati, Dwi; Dardanila, Dardanila; Lubis, Tasnim (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2024)
Riau Malay has language variations generating various dialects, including Pasir Pengaraian dialect, which reflects sound differences. To understand the characteristics of the dialect, it is necessary to analyze the sound changes from Proto Austronesian into Pasir Pengaraian Riau Malay dialect. The purpose of this research was first, to identify the sound changes of Proto Austronesian language into Riau Malay dialect of Pasir Pengaraian using Keraf's theory and second, to analyze the meaning changes that occur due to sound changes using Crowley & Bowern's theory. This research belonged to qualitative-descriptive research exploring thoroughly how sound changes from Proto Austronesian languages occured in detail and how these changes affect the meaning of words in cultural and social contexts which were then explained and described systematically. The data collection method used was interview method with listening technique, note-taking technique and recording technique by referring to the list of 200 Swadesh vocabularies. The results of the research obtained that (1) the types of sound changes of Proto Austronesian language into Riau Malay language were assimilation (progressive assimilation and palatalization), metathesis, afferesis, syncope, apocope, prothesis, epenthesis, paragogue, and monoftongization. (2) meaning changes that occur were pejoration, broadening, narrowing, and bifurcation.